2010
DOI: 10.1007/s11270-009-0320-5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Biofilm Treatment Systems on Particle Size Distribution in Three Wastewater Treatment Plants

Abstract: This article presents the results of a research study that analyzed the effect that secondary biofilm treatment systems had on particle size distribution (PSD) in the effluent of wastewater treatment plants. This study focused on three biofilm technologies (i.e. a submerged biofilter system, a trickling filter system, and a rotating biological contactor system) in three working urban wastewater treatment plants. For this purpose, the variation of the fit parameters was analyzed after modeling the PSD with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…According to [17], the prescribed value of EC, TSS, and TDS in drinking water is 400–1215  μ S/cm, 25–80 mg/L and <1000 mg/L, respectively. In this study, it was found that EC value of untreated wastewater decreased gradually during treatment due to the decrease in TDS and TSS levels as EC is directly dependent on the suspended and dissolved solids [18]. This decrease in EC might be related to the conversion of NO 3 into diatomic molecular nitrogen (N 2 ), which also decreases EC levels of domestic wastewater, that is, 113 mg/L (77.84%) with HRT of 20 days (Figure 2(b)).…”
Section: Resultsmentioning
confidence: 99%
“…According to [17], the prescribed value of EC, TSS, and TDS in drinking water is 400–1215  μ S/cm, 25–80 mg/L and <1000 mg/L, respectively. In this study, it was found that EC value of untreated wastewater decreased gradually during treatment due to the decrease in TDS and TSS levels as EC is directly dependent on the suspended and dissolved solids [18]. This decrease in EC might be related to the conversion of NO 3 into diatomic molecular nitrogen (N 2 ), which also decreases EC levels of domestic wastewater, that is, 113 mg/L (77.84%) with HRT of 20 days (Figure 2(b)).…”
Section: Resultsmentioning
confidence: 99%
“…EC is directly related to the suspended solids, dissolved solids and COD i.e. larger the number of suspended and dissolved solids in wastewater, higher will be the EC and vice versa [19]. In this study, it was found that EC value of untreated wastewater decreased gradually during treatment due to decrease in TDS and TSS levels.…”
Section: Analysis Of Water After Treatmentmentioning
confidence: 60%
“…During the treatment in the TF, turbidity of wastewater was completely removed with an efficiency of 100%. This might be due to the degradation of compounds in the wastewater by microorganisms during treatment [19,20,22].…”
Section: Analysis Of Water After Treatmentmentioning
confidence: 99%